2017
DOI: 10.3390/catal7050138
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-iron Oxide, Alloy and Nitride: Synthesis, Characterization and Application in Catalytic Peroxymonosulfate Activation for Orange II Degradation

Abstract: Abstract:In meeting the need for environmental remediation in wastewater treatment and the development of popular sulfate-radical-based advanced oxidation processes (SR-AOPs), a series of Co/Fe-based catalysts with confirmed phase structure were prepared through extended soft chemical solution processes followed by atmosphere-dependent calcination. Powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and 57 Fe Mössbau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 51 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…However, the traditional Fenton reaction encounters problems such as low pH conditions, sluggish Fe 3+ reduction kinetics and secondary pollutants caused by mass production of slurry containing Fe 3+ . Therefore, heterogeneous Fenton systems 1–3 in which Fe 2+ of the catalyst was replaced by Fe( ii ) active sites from solid iron metals, 4 alloys, 5–7 oxides 7–9 and other compounds are developed for better recyclability. Nevertheless, the rapid re-generation of Fe( ii ) active site from Fe( iii ) on the surface of heterogeneous Fenton catalysts remains challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional Fenton reaction encounters problems such as low pH conditions, sluggish Fe 3+ reduction kinetics and secondary pollutants caused by mass production of slurry containing Fe 3+ . Therefore, heterogeneous Fenton systems 1–3 in which Fe 2+ of the catalyst was replaced by Fe( ii ) active sites from solid iron metals, 4 alloys, 5–7 oxides 7–9 and other compounds are developed for better recyclability. Nevertheless, the rapid re-generation of Fe( ii ) active site from Fe( iii ) on the surface of heterogeneous Fenton catalysts remains challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The core-level Fe 2p XPS spectra of MLG-dppz@Fe were deconvoluted into three peaks: Fe 2p 3/2 and Fe 2p 1/2 regions at 712.5 eV and 725.8 eV, respectively, assigned to the Fe(III) formal oxidation state, and the characteristic Fe 3+ 2p 3/2 satellite peak centered at 719.1 eV, in agreement with previously reported studies. [98][99][100][101][102][103] The Fe 2p XPS spectra of MLG-dppz@Fe(240N 2 ) and MLGdppz@Fe(240air) were tted into ve characteristic contributions (Fe 2+ 2p 3/2 , Fe 3+ 2p 3/2 , satellite peak, Fe 2+ 2p 1/2 , and Fe 3+ 2p 1/2 ). The generation of Fe 2+ species and the binding energies at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks located at 711.9-712.1 eV, 710.4-710.7 eV, and 709.1-709.4 eV are the assigned as FeOOH, Fe(III) in Fe 2 O 3 , and Fe(II) peak, respectively. [28][29][30][31] The peak intensity and area changes indicated that Fe(II) mostly existed in the specimens obtained under dark conditions (Figs. 4(a), 4(b)), while more FeOOH and Fe 2 O 3 exist under light irradiation compared with that under dark conditions.…”
Section: Resultsmentioning
confidence: 99%